2019
DOI: 10.1016/j.schres.2018.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Altered short-term neural plasticity related to schizotypal traits: Evidence from visual adaptation

Abstract: Abnormalities in synaptic plasticity are argued to underlie the neural dysconnectivity observed in schizophrenia. One way to measure synaptic plasticity is through sensory adaptation, whereby sensory neurons exhibit reduced sensitivity after sustained stimulus exposure. Evidence for decreased adaptation in individuals with schizophrenia is currently inconclusive, possibly due to heterogeneity in clinical and medication status across samples. Here we circumvent these confounds by examining whether altered adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 81 publications
(101 reference statements)
0
14
1
Order By: Relevance
“…Findings in non-clinical samples may provide further insights into a potential role of medication. In an undergraduate sample, we found that the strength of tilt aftereffects, but not negative afterimages, was related to schizotypal traits (Thakkar, Antinori, et al, 2019). However, the direction of that relationship was opposite to what the current findings would predict; increased schizophrenia-like traits were associated with weaker tilt aftereffects.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Findings in non-clinical samples may provide further insights into a potential role of medication. In an undergraduate sample, we found that the strength of tilt aftereffects, but not negative afterimages, was related to schizotypal traits (Thakkar, Antinori, et al, 2019). However, the direction of that relationship was opposite to what the current findings would predict; increased schizophrenia-like traits were associated with weaker tilt aftereffects.…”
Section: Discussioncontrasting
confidence: 99%
“…To ensure data quality, we applied several previously employed data exclusion criteria, (Brascamp, Becker, & Hambrick, 2018;Thakkar, Antinori, Carter, & Brascamp, 2019), which are detailed in the Supplemental Methods. 3 PSZ and 1 HC were excluded from the negative afterimage analysis (leaving a total sample of 33 PSZ and 21 HC), and 6 PSZ and 1 HC were excluded from the tilt aftereffect analysis (leaving a total sample of 30 PSZ and 21 HC).…”
Section: Quantifying Aftereffectsmentioning
confidence: 99%
“…Anxiety patients have been shown to have faster durations (Nagamine et al, ). Individuals with higher schizotypal traits show a higher proportion of mixed percepts during rivalry (Thakkar, Antinori, Carter, & Brascamp, ). A study looking at the Big Five personality scale found that industrious or self‐disciplined people had longer perceptual durations during rivalry (Antinori, Smillie, & Carter, ).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals diagnosed with bipolar disorder have repeatedly been shown to have slower durations compared to controls (Miller et al, 2003;Nagamine, Yoshino, Miyazaki, Takahashi, & Nomura, 2009;Ngo, Mitchell, Martin, & Miller, 2011;Pettigrew & Miller, 1998;Vierck et al, 2013), as have those diagnosed with autism (Robertson, Kravitz, Freyberg, Baron-Cohen, & Baker, 2013); however see, (Said, Egan, Minshew, Behrmann, & Heeger, 2013) to have faster durations (Nagamine et al, 2007). Individuals with higher schizotypal traits show a higher proportion of mixed percepts during rivalry (Thakkar, Antinori, Carter, & Brascamp, 2018). A study looking at the Big Five personality scale found that industrious or self-disciplined people had longer perceptual durations during rivalry (Antinori, Smillie, & Carter, 2017).…”
Section: Binocular Rivalry Alpha Frequency Mental Disorders and mentioning
confidence: 99%
“…Previous research on selective attention demonstrates marked malleability of neural systems in charge of potential changes in response to intervention [16]. Dysplasticity in schizophrenia has been known for decades, and while it has predominantly been reported in motor and frontal areas [17,18], it is also expressed in multiple brain regions including sensory systems [19]. The underlying mechanism of neuroplasticity-based CCT is meant to induce widespread changes in both cortical and subcortical representations and may not be captured by singleregion activation maps measured by task-based MRI [3,20,21].…”
Section: Introductionmentioning
confidence: 99%